Pemanfaatan Cloud Service Dan Nodemcu Pada Internet of Things - Dody Hidayat; Liza Fitriana; Andi Marwan Elhanafi; Stephanus Priyowidodo; R Ramli (LPPM STIKOM Tunas Bangsa, 2022)
The Internet of Things is a growing field of research in the era of globalization revolution 4.0. The development of information technology is also developing human interests and abilities regarding information technology, seen from several aspects that make human competitiveness superior. Internet of Things is a concept that optimizes internet connectivity in enabling humans to interact with electronic equipment connected to the internet network. The use of computers in the future will dominate human work to control electronic equipment remotely. To apply the Internet of Things concept, devices that are able to work optimally are needed, such as the NodeMCU as Hardware in a Microcontroller circuit in which a System on Chip (SoC) is embedded, namely the Wifi module and also a Blynk App Software to control the work of the Hardware. The Informatics Management Study Program community service team at Harapan University in Medan conducted socialization regarding the Internet of Thing at SMA N 13 Medan with the aim of introducing and increasing students' knowledge and skills in the field of information technology, especially in the Internet of Things. This service is carried out by the socialization method, namely lectures, demonstrations and questions and answers. The results of the activities that have been carried out went well and were successful, the activity of the participants was very high, this was seen from the many questions asked when the question and answer session opened..